2020
DOI: 10.1177/0846537120929429
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Center Experience With Percutaneous Interventional Management of Refractory Chylous Ascites

Abstract: Purpose: Management of chylous ascites is poorly understood with no management guidelines. We retrospectively reviewed patients treated for chylous ascites at our institution to evaluate efficacy and safety of lipiodol lymphangiography and embolization. Materials and Methods: Seven patients underwent percutaneous interventional management of chylous ascites (average age 52.5 years, 3 female, 6 post-surgical, 1 pancreatitis) from 2012. All patients underwent lipiodol inguinal lymph node injection. Adjunctive gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Pan et al [ 22 ] revealed that in treating CA, enteral nutrition (EN) + medium-chain triglyceride (MCT) instead of total parenteral nutrition (TPN) was the best nutritional support and somatostatin should be used immediately. Aalami et al [ 23 ] published a large review of 156 cases and concluded that the resolution rate of conservative treatment was 67% while the remaining 33% of patients required surgical intervention such as lymphangiography and embolization[ 24 ]. The patients with CA that we included in this study were all cured by conservative treatment, such as diet control and the administration of somatostatin or its synthetic derivatives but the hospital stay was significantly prolonged with an average length of stay of 15.7 d, leading to a significant increase in hospital costs and was not conducive to the turnover rate of hospital beds.…”
Section: Discussionmentioning
confidence: 99%
“…Pan et al [ 22 ] revealed that in treating CA, enteral nutrition (EN) + medium-chain triglyceride (MCT) instead of total parenteral nutrition (TPN) was the best nutritional support and somatostatin should be used immediately. Aalami et al [ 23 ] published a large review of 156 cases and concluded that the resolution rate of conservative treatment was 67% while the remaining 33% of patients required surgical intervention such as lymphangiography and embolization[ 24 ]. The patients with CA that we included in this study were all cured by conservative treatment, such as diet control and the administration of somatostatin or its synthetic derivatives but the hospital stay was significantly prolonged with an average length of stay of 15.7 d, leading to a significant increase in hospital costs and was not conducive to the turnover rate of hospital beds.…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, a feasible alternative is percutaneous interventional management. 7 Although the indications for this approach are varied, some authors have proposed its use with drainage of 1000 mL/day for 45 days or persistent drainage lasting more than 1–2 weeks despite conservative treatment. 8 Fewer than 100 cases have been described in the literature.…”
Section: Case Presentationmentioning
confidence: 99%
“…Different authors have reported success rates with lymphangiography and embolization between 35–86%, without significant minor or major complications. 7 9 Even performing repeat procedures, clinical success is achieved in up to 86% of cases, without adverse events. 9 Complications following lymphangiography are rare.…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymphangiography and percutaneous embolization are a less invasive procedure and have been reported to have a therapeutic effect in 56-86% of patients with lymphatic leaks 1,2 . Intranodal lymphatic embolization has been previously described in the treatment of some visceral lymphatic leaks 1,5,13 . This study aimed to present a case of chylous ascites after pancreatoduodenectomy treated with lipiodol lymphangiography and embolization.…”
Section: Introductionmentioning
confidence: 99%